Nutritional considerations for the prevention and treatment of postmenopausal osteoporosis. Issue 7 (July 2020) - Grippe, Kristen; Ryan, Victoria
Abstract : ABSTRACT: Osteoporosis commonly affects postmenopausal women and accounts for 300, 000 hip fractures in the United States each year. More women are deferring or discontinuing pharmacologic treatment because of intolerable adverse reactions or fear of long-term safety. Supplementing dietary intake of certain vitamins and minerals can have positive effects on bone parameters. Calcium is frequently recommended for osteoporotic patients but many not confer much benefit toward bone density. Certain forms of vitamins A and K have been shown to increase bone density. Isoflavones and phytates are phytochemicals found in soy foods that are comparable to bisphosphonates when consumed at certain levels. Lastly, increasing certain daily fruit and vegetable servings can improve bone health. Nutritional interventions are typically safe alternatives that should be considered for postmenopausal women who are seeking nonpharmacologic treatment options for osteoporosis.